(untitled) - Panayotis P Kelalis (London, 1992)
All chapters in this book have been completely rewritten, in many instances by new authors, thus bringing the subject matter up to date, clearly reflecting the changes in the field, and adding a new perspective in the approach to the clinical problems.
Keywords: pediatric urolory,urologic diseases - in infancy and childhood